Analytical electron microscopy study on gallium nitride systems doped with manganese and iron. (8th January 2015) - Meingast, Arno; Navarro Quezada, Andrea; Devillers, Thibaut; Kovács, András; Albu, Mihela; Fladischer, Stefanie; Bonanni, Alberta; Kothleitner, Gerald
Abstract: Modulated structures of gallium nitride (GaN) doped with transition metal ions (here Fe, Mn) are investigated by analytical (scanning) transmission electron microscopy to gain insight into the structural arrangement and chemical composition of the material, known to be critically correlated to the magnetic response and hence the functionality of these technologically relevant systems. Three classes of samples are considered: (i) homogeneous (dilute) (Ga, Mn)N; (ii) δ -Mn-doped (Ga, δ -Mn)N and phase separated (Ga, Fe)N, containing Fe-rich nanocrystals. The combination of various microscopic techniques employed, allows for a quantitative determination of the distribution of the magnetic ions in the samples, providing essential information on the structural and chemical asset of these systems.